A long-term drought assessment over India using CMIP6 framework : present and future perspectives - VERMA, AASHNA; VISHWAKARMA, AKASH; BIST, SANJAY; KUMAR, SUSHIL; BHATLA, RAJEEV (MAUSAM, 2023)
Research on the characteristics and spread of droughts has progressed significantly for future climate scenarios. However, studies on drought mitigation in relation to climate change have been largely inadequate. This study focuses on the severity and frequency of drought events based on meteorological properties of drought under two climate change scenarios: Shared Socioeconomic Pathway (SSP2 4.5 and SSP5 8.5). We utilized the Sixth International Coupled Model Inter-comparison Project sixth phase (CMIP6) ensemble General Circulation Models (GCMs) to collect historical (1901-2014) and future (2025-2100) precipitation data. IMD gridded precipitation was used as a reference data for comparative studies. We constructed the Standardized Precipitation Index (SPI) under two different Socioeconomic Shared Pathways (SSPs) to analyze future drought scenarios in the Indian region. Our results show a gradual increase in SPI values for future years, indicating an increase in the severity of drought events in the Indian region. The increase is more pronounced under the SSP5 8.5 scenario, which assumes high greenhouse gas emissions and limited climate change mitigation efforts. Furthermore, our results suggest that major dry spells are likely to occur in the first half of the future period, particularly in the case of ACCESS-ESM, one of the GCMs used in our analysis. In contrast, the NOR-ESM-MM model indicates that dry spells are anticipated throughout the entire future period. Overall, our study provides valuable insights into the potential impacts of climate change on drought events in the Indian region.